Principles of Macroeconomics 2e support material for OpenStax textbook: week 8, chapter 13 - OER project materials - Miller, Ray, author; Bhattarai, Niroj, author; Nunes, Débora, author (Colorado State University. Libraries, 2023)
Week 8 discussion: The Keynesian versus the neoclassical perspective (chapter 13). The material included here was developed to support the use of the OpenStax textbook Principles of Macroeconomics 2e. The material includes two components: (1) weekly discussion prompts that were developed for use on online discussion boards; and (2) weekly recitation worksheets and answer keys.

Please see online textbook: https://openstax.org/details/books/principles-macroeconomics-2e.
Missing weeks are exam review weeks. There is a discussion prompt but no recitation material for week 4 (exam review).
ECON 204.
Keywords: Economics -- Study and teaching (Higher)